Indications for Thoracic EndoVascular Aortic Repair (TEVAR): A Brief Review - Manetta, Frank; Newman, Joshua; Mattia, Allan (International Journal of Angiology, 2018)
The utility of Thoracic EndoVascular Aortic Repair (TEVAR) continues to progress at a very rapid rate. Initially implemented for the treatment of thoracic aortic aneurysms, TEVAR has evolved to treat a variety of aortic pathologies and reduce overall morbidity and mortality rates compared with traditional open surgical repair.Given the rapidly evolving nature of endovascular thoracic intervention, we hereby briefly review the current literature on the evolving applications of TEVAR.TEVAR continues to rapidly evolve and is being applied to a growing number of aortic pathologies. Given the perioperative, short- and mid-term morbidity and mortality rates, TEVAR is quickly surpassing traditional open surgical intervention as the ideal procedure for patients undergoing intervention of the descending thoracic aorta and applicability to ascending and arch pathologies is being explored. However, as more data becomes available TEVAR may be associated with higher rates of reoperative requirements. Data remains limited on the long-term efficacy of the intervention and should continue to be investigated.
Keywords: aneurysm; aortic dissection; endograft placement; endovascular repair; TEVAR; pseudoaneurysm